2023
DOI: 10.26907/2542-064x.2023.2.231-262
|View full text |Cite
|
Sign up to set email alerts
|

Plant Microbiome: Origin, Composition, and Functions

Abstract: Microorganisms play an important role in the growth and development of a plant throughout its entire life cycle. Recent advances in the methods of molecular biological analysis have expanded our understanding of the composition and functions of plant microbiota (epiphytic, rhizosphere, and endosphere) and the molecular mechanisms associated with specific processes that govern plant-microorganism interactions. This article reviews the types of plant microbial communities, their sources of origin, and species co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The number of OTUs in the soil of the control variant was higher than that in the water of the control variant of the hydroponic experiment. However, in leaves and roots, the number of OTUs was similar for both soil and hydroponic experiments since the endophytic bacterial community of plants is determined mainly by the composition of the seed bacterial community [35]. It was found that the greatest diversity of the bacterial community was in the soil samples, and the least was in the samples of the leaves and roots of lettuce.…”
Section: Soil Experimentsmentioning
confidence: 90%
See 2 more Smart Citations
“…The number of OTUs in the soil of the control variant was higher than that in the water of the control variant of the hydroponic experiment. However, in leaves and roots, the number of OTUs was similar for both soil and hydroponic experiments since the endophytic bacterial community of plants is determined mainly by the composition of the seed bacterial community [35]. It was found that the greatest diversity of the bacterial community was in the soil samples, and the least was in the samples of the leaves and roots of lettuce.…”
Section: Soil Experimentsmentioning
confidence: 90%
“…As a result, the endophytic community of an adult plant consists of the species present in the seed and the species present in the substrate. A small proportion of the community is also occupied by accidentally penetrating species (for example, from the air through damage in plant cells) [32,35].…”
Section: Hydroponic Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to modern understanding, microorganisms residing within plants play an equally significant role as the plant's own tissues and organs. Indeed, the endophytic microbiome plays a crucial role in promoting plant growth (PGP) and combating phytopathogens [44,45]. Endophytes can directly influence plant growth by producing phytohormones (e.g., jasmonic and salicylic acids) and inhibit the production of plant cells' ethylene.…”
Section: Influence Of Glda-chelate Fertilization On Leaf and Root End...mentioning
confidence: 99%